2013
DOI: 10.1590/s0103-84782013000900029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of sodium metabisulphite and chlorine on growth of Aspergillus spp. and Penicillium spp. strains isolated from marine shrimp

Abstract: The sodium metabisulphite (SMB) is used in shrimp farming to prevent melanosis and the 5.0 ppm chlorine (CL) concentration used in the shrimp processing is efficient as a bactericide, but there is no evidence of the effectiveness of these chemical compounds as fungicides. Therefore, the aim of this study was to evaluate the in vitro effect of sodium metabisulphite (SMB) and chlorine (CL) on the growth of Aspergillus and Penicillium species isolated from marine shrimp in different stages of processing. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Other more specific studies on the efficacy of SO2 on growth of A. flavus strains have predominantly focused on mycelial growth only, and not on AFs production. For example, Santos et al (2013) suggested that in vitro growth of A. flavus isolated from marine shrimp was inhibited when exposed to 10% NaMBS. Chourasia (1993) found that mycelial growth of Aspergillus parasiticus was completely inhibited by 0.1% of NaMBS but no account of abiotic factors, especially temperature x aw, were taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Other more specific studies on the efficacy of SO2 on growth of A. flavus strains have predominantly focused on mycelial growth only, and not on AFs production. For example, Santos et al (2013) suggested that in vitro growth of A. flavus isolated from marine shrimp was inhibited when exposed to 10% NaMBS. Chourasia (1993) found that mycelial growth of Aspergillus parasiticus was completely inhibited by 0.1% of NaMBS but no account of abiotic factors, especially temperature x aw, were taken into account.…”
Section: Introductionmentioning
confidence: 99%